Analysis of weighted gene co-expression networks and clinical validation identify hub genes and immune cell infiltration in the endometrial cells of patients with recurrent implantation failure - Liu, Zhenteng; Lai, Shoucui; Qu, Qinglan; Liu, Xuemei; Zhang, Wei; Zhao, Dongmei; He, Shunzhi; Sun, Yuxia; Bao, Hongchu (Frontiers in Genetics, 2024)
Background: About 10% of individuals undergoing in vitro fertilization encounter recurrent implantation failure (RIF), which represents a worldwide social and economic concern. Nevertheless, the critical genes and genetic mechanisms underlying RIF are largely unknown. between hub genes and other genes and key pathways.We first utilized WGCNA to identify the most potential nine hub genes which might be associated with RIF. Meanwhile, this study offers insights into the landscape of immune infiltration status to reveal the underlying immune pathogenesis of RIF. This may be a direction for the next study of RIF etiology. Further studies would be required to investigate the involved mechanisms.